THE EFFECT OF TRAINING ON EMPLOYEE PERFORMANCE AT THE LAWAWOI COMMUNITY HEALTH CENTER, SIDENRENG RAPPANG DISTRICT - A. Nabilah Ainun Zahrani; Gazali Amin; Suriadi Suriadi (Jurnal Mahasiswa Manajemen, 2024)
The Effect of Training on Employee Performance at the lawawoi Community Health Center, Sidenreng Rappang district. This study aims to examine the effect of training on Employee performance is important for the success of the agency. Training can improve performance, but many agencies ignore it to test whether training affects employee performance at the lawawoi community health center, sidenreng rappang district. The research method used is quantitative. The data used primary data obtained from questionnaires. The population of this study was 128 respondents, sampling using saturated sampling. The data obtained was processed using the SPSS program. The data analysis method used is simple regression analysis. The results of the study interpret that the effect of training on employee performance at the lawawoi community health center, sidenreng rappang district has a significant effect on employee performance, so the hypothesis in this study is accepted.